Adjuvant immunotherapy of C6 glioma in rats with pertussis toxin - Orozco-Morales, Mario; Sánchez-García, Francisco-Javier; Guevara-Salazar, Patricia; Arrieta, Oscar; Hernández-Pedro, Norma Y.; Sánchez-García, Aurora; Perez-Madrigal, Rodolfo; Rangel-López, Edgar; Pineda, Benjamín; Sotelo, Julio (Journal of cancer research and clinical oncology, 2012)
Purpose In spite of the recent advances in surgery and antitumor drugs, the brain tumors, like glioblastoma, have shown a poor prognosis. The aim of this study was to determine the effect of pertussis toxin (PTx) as immunomodulatory molecule on glial tumors induced by C6 glioma cells. Methods Given the pleiotropic effect of PTx on the immune system, we analyzed the effect of PTx on CD4+/CD25+/FoxP3+ (Treg) cells like as immunotherapeutic adjuvant. Thirty rats with a glial tumor of 1.5 cm in diameter were separated in two groups: the first group was treated with PTx and the second group was non-treated (controls). Tumoral volume was measured weekly; tumor, blood and spleen were taken for analysis of subpopulations of T cells, apoptotic index and cytokine contents, in both groups. Results We observed a significant decrease in tumor volume in the PTx group; this was associated with a decreased in the number of Treg cells, in both spleen and tumor. The percentage of apoptotic cells was increased as compared with that of controls. The production of proinflammatory cytokines was increased in mRNA for IL-6 as well as a small increase in the mRNA expression of perforin and granzime in tumors from rats treated with PTx. No changes were found in the mRNA expression of MCP-1 and MIP-1α. Conclusion These results suggest that PTx could be an immunotherapeutic adjuvant in the integral therapy against glial tumors.